Iron status and anemia control are related to peritoneal membrane properties in peritoneally dialyzed patients - Tomasz Głogowski; Ewa Wojtaszek; Jolanta Malyszko (Frontiers in Medicine, 2023)
BackgroundCharacteristics of peritoneal membrane is unique and individually different in peritoneal dialysis patients. Relationship between specific nature of peritoneal transport, anemia and inflammation has not yet been extensively studied. We attempted to outline the complex interplay of several biomarkers of iron status and their association with peritoneal transport, degree of inflammation and residual renal function.MethodsA total of 58 patients treated with peritoneal dialysis either CAPD or APD for at least 3 months were enrolled in this study. Full blood count, traditional markers of iron status (transferrin saturation-TSAT and ferritin), serum erythroferrone-ERFE, soluble transferrin receptor (sTfR), hepcidin, zonulin, growth differentiation factor −15 (GDF15), IL-16, hsCRP and hypoxia-inducible factor—α (HIF-1-α; in serum and dialysate) were measured using commercially available tests. We also performed Peritoneal Equilibrium Test and assessed GFR level.ResultsHb levels above 10 g/dL was found in 74% of patients. Hb levels positively correlated with residual renal function and nutritional status. Adequate iron status was diagnosed in 69% of subjects, only in 9% of patients, criteria for absolute iron deficiency were met. Serum ERFE correlated inversely with hepcidin levels but was not associated with erythropoietin stimulating agent dose. Peritoneal transport had strong correlation with dialysate sTfR (p < 0.05), dialysate hepcidin (p < 0.05), dialysate GDF15 (p < 0.01) and dialysate zonulin (p < 0.001) levels, as well as serum IL6 (p = 0.03), serum hs-CRP (p = 0.04) and dialysate hs-CRP (p = 0.04).ConclusionResidual kidney function contributes considerably to better control of anemia. Various degree of inflammation is inherent to PD patients. Additionally, fast-average peritoneal transport is associated with greater degree of inflammation and higher concentration of markers of iron status, GDF15 and zonulin in dialysate. This finding may indicate more effective clearance of higher-range middle molecules in fast-average transporters. The role of ERFE as a marker of erythropoiesis in PD patients requires further investigation.